2022
DOI: 10.1002/adma.202203104
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Regulated Electrostatic Shielding Layer toward Dendrite‐Free Zn Batteries

Abstract: Although aqueous Zn batteries have become a more sustainable alternative to lithium‐ion batteries owing to their intrinsic security, their practical applications are limited by dendrite formation and hydrogen reactions. The first application of a rare earth metal type addition to Zn batteries, cerium chloride (CeCl3), as an effective, low‐cost, and green electrolyte additive that facilitates the formation of a dynamic electrostatic shielding layer around the Zn protuberance to induce uniform Zn deposition is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(96 citation statements)
references
References 42 publications
0
73
0
Order By: Relevance
“…Apparently, when ImS/ZSO electrolyte was used, the cell delivered over 2100 plating/stripping cycles with an ultrahigh average CE of 99.9%, which further demonstrates the inhibitory effect of ImS additive on parasitic reactions. The CE of the Zn//Cu cell in ImS/ZSO electrolyte can still reach ∼99.8% after 200 cycles and even the current density and capacity are increased to 40 mA cm −2 and 10 mA h cm −2 , which outperform the current study 19,37,50–54 (Fig. 3i).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Apparently, when ImS/ZSO electrolyte was used, the cell delivered over 2100 plating/stripping cycles with an ultrahigh average CE of 99.9%, which further demonstrates the inhibitory effect of ImS additive on parasitic reactions. The CE of the Zn//Cu cell in ImS/ZSO electrolyte can still reach ∼99.8% after 200 cycles and even the current density and capacity are increased to 40 mA cm −2 and 10 mA h cm −2 , which outperform the current study 19,37,50–54 (Fig. 3i).…”
Section: Resultsmentioning
confidence: 78%
“…5f. In the pure ZSO electrolyte, the current density at the tip of the Zn dendrite was higher than that at other locations, indicating a remarkably uneven localized electric field with intensity increase at the surface protuberance sites, 54,73 which is significantly improved to uniformity in the ImS/ZSO electrolyte. The ImS additive with a π–π conjugation imidazolium cation provides a positively charged electrostatic layer, which leads to an even distribution of the Zn 2+ on the interface, and thus the uniform current density distribution.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the results showed that the surface of the Zn electrode in ULE did not detect the expected SEI and was not significantly different from the Zn electrode in the pristine electrolyte (Figures S14 and S15). Therefore, we speculate that the texture orientation may be attributed to the electrostatic shielding effect brought by Li + , according to previous research. Considering that both the (101) and (100) planes are inclined or vertical to the Zn plate, it inevitably leads to the tip effect that makes the Li + adsorb on the edge and tip, inhibiting their further growth. Since Li + suppresses the deposition of (101) and (100) planes caused by concentration polarization, Zn crystals retain the tendency to deposit on the lowest surface energy (002) planes to the maximum extent .…”
mentioning
confidence: 63%
“…4 Therefore, it is urgent to develop new battery systems with high energy densities, long lifespans, and the absence of safety issues. 5 Rechargeable aluminum-ion batteries (AIBs) are considered to be one of the most attractive alternatives due to their distinctive advantages of low cost, high safety and environmental friendliness. 6 However, the study of AIBs is still in its infancy.…”
mentioning
confidence: 99%